Imaging When Acting: Picture but Not Word Cues Induce Action-Related Biases of Visual Attention - Wykowska, Agnieszka; Hommel, Bernhard; Schubö, Anna (Frontiers in Psychology, 2012)
In line with the Theory of Event Coding (Hommel et al., 2001), action planning has been shown to affect perceptual processing—an effect that has been attributed to a so-called intentional weighting mechanism (Memelink & Hommel, in press; Wykowska, Schubö, & Hommel, 2009), whose functional role is to provide information for open parameters of online action adjustment (Hommel, 2010). The aim of this study was to test whether different types of action representations induce intentional weighting to various degrees. To meet this aim, we introduced a paradigm in which participants performed a visual search task while preparing to grasp or to point. The to-be performed movement was signaled either by a picture of a required action or a word cue. We reasoned that picture cues might trigger a more concrete action representation that would be more likely to activate the intentional weighting of perceptual dimensions that provide information for online action control. In contrast, word cues were expected to trigger a more abstract action representation that would be less likely to induce intentional weighting. In two experiments, preparing for an action facilitated the processing of targets in an unrelated search task if they differed from distractors on a dimension that provided information for online action control. As predicted, however, this effect was observed only if action preparation was signaled by picture cues but not if it was signaled by word cues. We conclude that picture cues are more efficient than word cues in activating the intentional weighting of perceptual dimensions, presumably by specifying not only invariant characteristics of the planned action but also the dimensions of action-specific parameters.